Advanced Treatment and Imaging in Colonoscopy: The Pocket-Creation Method for Complete Resection and Linked Color Imaging for Better Detection of Early Neoplastic Lesions by Colonoscopy - Hironori Yamamoto; Satoshi Shinozaki; Yoshikazu Hayashi; Yoshimasa Miura; Tsevelnorov Khurelbaatar; Hiroyuki Osawa; Alan Kawarai Lefor (Korean Society of Gastrointestinal Endoscopy, 2019)
Early detection and resection of neoplastic lesions are key objectives to diminish colorectal cancer mortality. Resection of superficial colorectal neoplasms, cold snare polypectomy, endoscopic mucosal resection, and endoscopic submucosal dissection have all been developed and used worldwide. The pocket-creation method facilitates the resection of tumors in difficult and routine locations. Early detection is the most important first step to maximize the benefits of recent advancements in endoscopic techniques. However, the detection of small, flat-shaped, or faded color lesions remains difficult. Linked color imaging, a novel multi-light technology, facilitates the recognition of minor differences in tissue by enhancing the color contrast between early colorectal neoplasms and surrounding normal mucosa in a bright field of view. The most striking feature of linked color imaging is its ability to display the color of early neoplastic lesions as distinct from inflammatory changes, both of which have similar "redness" when viewed using white light imaging. To increase the detection rate of neoplasms, linked color imaging should be used from the outset for endoscopic observation. Early detection of superficial colorectal tumors can result in decreased mortality from colorectal cancer and maintain a good quality of life for patients.